Inflammatory gene polymorphisms and ischaemic heart disease: review of population association studies. Issue 2 (1st February 2002) - Andreotti, F; Porto, I; Crea, F; Maseri, A
Abstract : Inflammation and genetics are both prominent mechanisms in the pathogenesis of atherosclerosis and arterial thrombosis. Accordingly, a number of population studies have explored the association of ischaemic heart disease with gene polymorphisms of the inflammatory molecules tumour necrosis factors (TNF) α and β, transforming growth factors (TGF) β1 and 2, interleukin (IL) 1 and its receptor antagonist (IL 1ra), CD14 (the receptor for lipopolysaccharide), P and E selectins, and platelet endothelial cell adhesion molecule (PECAM) 1. Although they are very preliminary and partly conflicting, the data provide some evidence that alterations in the genetics of the inflammatory system may modify the risk of ischaemic heart disease.